Epidemiologic Investigation of Foodborne Outbreaks in Pharmacies: A Pilot Study - Torre, Carla (2015)
Introduction: The analysis of Foodborne Outbreaks (FBO) investigation data provides knowledge on food vehicles and contributive factors of human infections allowing their risk management. However, FBO are commonly underreported and alternative sources of information may prove useful. Purpose: To test the adequacy of Pharmacies as an information source to identify foods involved in FBO, their confection type and acquisition place as well as the main symptoms and medicines taken. Methods: Application of a FBO epidemiologic investigation inquiry to individuals with FBD suggestive symptoms that went to 249 Pharmacies all over Portugal looking for treatment, between 18th August and 15th de November 2014. Descriptive statistical analysis of the results was performed and absolute and relative frequencies measures of location and dispersion were calculated in the program SAS version 9.1. Results: From 270 validated inquiries collected online until 29 October, 72.9% of the individuals went to the Pharmacy as the first health resort (average age 44.1 years), 56.3% individuals reported moderate symptoms, namely diarrhea and 58.0% of individuals took anti-diarrheal. The most frequent place of consumption of the suspect food was home (51.5 %), restaurants (22.9%) and parties (13.4%) and the food was meat (21.6%) and vegetables (18.3%), mostly cooked. About 67% of the individuals reported that an average of other 4.6 individuals has consumed the same food and 29.6% of them showed the same symptoms. Significance: The findings are consistent with the Portuguese FBO investigation data reported to EFSA and therefore indicate that Pharmacies can be a valuable source of information about FBO and also support consumer food safety education in order to prevent FBO.